Professional AngularJS - Karpov, Valeri; Netto, Diego (New Delhi Wiley, 2017)
AngularJS is quickly becoming the leading next-generation client-side web framework, enabling the building and testing of sophisticated browser-based applications. This book covers everything from building your first AngularJS application to more advanced topics like transclusion, build systems, and automated integration testing.
Building a simple AngularJS application -- Intelligent workflow and build tools -- Architecture -- Data binding -- Directives -- Templates, location, and routing -- Services, factories, and providers -- Server communication -- Testing and debugging AngularJS applications -- Moving on.
Includes index.
Keywords: Application software -- Development; JavaScript (Computer program language); Application software -- Development; JavaScript (Computer program language); AngularJS (Software framework); AngularJS (Software framework)